Feeling (with) Japan: affective, sensory and material entanglements in the field. Issue 3 (3rd July 2019) - De Antoni, Andrea; Cook, Emma E.
Abstract: This introduction provides a literature review on the anthropology of the senses and affect, highlighting the theoretical and methodological issues, and pointing at the ideas of "affective practices" or "practices of feeling with the world" as possible solutions. Subsequently, it reviews the literature related to these topics focusing on Japan, showing existing gaps in research. Lastly, it provides an overview of the contributions, in order to set the topic and clarify the reasons why we advocate for a novel approach revolving around "feeling (with) Japan."